Predictors of HIV Preexposure Prophylaxis Initiation Among Public Health Clients in Rural and Small Urban Areas in Iowa. (March 2021) - Howren, M. Bryant; Francis, Shelby L.; Polgreen, Linnea A.; Shafer, Cody; Hoth, Angela; Ohl, Michael E.
Objective: Preexposure prophylaxis (PrEP) is a safe and effective method for HIV prevention, but little is known about PrEP uptake in rural and small urban areas. We described rates and predictors of HIV PrEP initiation among public health clients in rural and small urban areas in Iowa. Methods: This was a prospective cohort study of clients with PrEP indications served by HIV testing and disease intervention specialist/partner services (DIS/PS) programs in public health departments in Iowa from February 1, 2018, through February 28, 2019. Eligible participants were aged 18-70 and referred for PrEP by public health personnel. Participants completed surveys at enrollment addressing demographic characteristics; sexual history; previous drug use; PrEP experiences; and knowledge, attitudes, and beliefs about PrEP. A follow-up survey assessed PrEP initiation at 30 days. We compared baseline characteristics of PrEP initiators and non-initiators. Results: Two hundred thirty-four public health clients consented to participate in the study; 189 completed the baseline survey, and 117 (61.9%) completed the follow-up survey. The mean age of participants in the baseline survey was 30 (range, 18-68); 109 (57.7%) were male, 127 (67.2%) were White, and 169 (89.4%) lived in a rural or small urban area. Of 117 participants in the follow-up survey, those who initiated PrEP were significantly more likely than those who did not initiate PrEP to be referred by DIS/PS programs (46.7% vs 7.8%, P < .001) and to recognize that PrEP was ≥90% effective (86.7% vs 35.3%, P = .001). No PrEP initiators and 8 PrEP non-initiators agreed that PrEP is for promiscuous people (0% vs 7.8%, P = .04). Perceived PrEP stigma was low and not associated with PrEP initiation. Conclusions: PrEP initiation rates were low among rural and small urban health department clients. Interventions are needed to improve linkage to PrEP among rural and small urban public health clients.